HOW ISLAMIC VALUE IMPLIED BUSINESS ACTIVITY ON MOSLEM WOMEN ENTREPRENEURS - Dwi Prasetyani; Khusnul Ashar; Susilo S; Multifiah M (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
This study aims to understand the implementation of Islamic values by Moslem women entrepreneurs in Surakarta that carried out in their business activities. Understanding Islamic value in their business activities showed from management, employee and financial aspects. Perception of Islamic values underlie the behavior of Moslem women entrepreneurs especially in their business activities. This study used qualitative method and phenomenology design to understand the behavior Moslem women entrepreneurs. Phenomenological approach appropriate to explore that embedded behind the human mind. This study found that Moslem women entrepreneurs have tried to apply Islamic values in the three aspects of business activities. There is a behavioral transformation caused by experience, understanding of Islamic Value, internal and external environment, belief in value. Transformation visible on intentions, motivations, and goals which is manifested in behavior. The process of this transformation there is time difference between one another which known as hidaya